The cross-talk between matrix metalloproteinase-9, RANKL/OPG system and cardiovascular risk factors in ovariectomized rat model of postmenopausal osteoporosis. - Maha Sabry (Public Library of Science (PLoS), 2021)
Epidemiology and pathogenesis of cardiovascular diseases (CVD) and osteoporosis are strikingly overlapping. This study presents matrix metalloproteinase-9 (MMP-9), as a simple molecular link more consistently associated with the pathophysiology of both osteoporosis and CVD risk factors. 40 adult female rats were randomly distributed into 4 groups [control sham-operated, untreated osteoporosis, carvedilol-treated osteoporosis and alendronate-treated osteoporosis]. After 8 weeks, blood samples were collected to estimate Lipid profile (Total cholesterol, HDL, Triglycerides), inflammatory markers (IL-6, TNF alpha, CRP and NO), and Bone turnover markers (BTM) (Alkaline phosphatase, osteocalcin and pyridinoline). The tibias were dissected to estimate MMP-9 and NF-kB gene expression, OPG, RANKL levels and for histological examination. Induction of osteoporosis resulted in a significant elevation in BTM, inflammatory markers and dyslipidemia. MMP-9 was significantly elevated and positively correlated with BTM, inflammation and dyslipidemia markers. Carvedilol and alendronate exerted a bone preservative role and attenuated dyslipidaemia and inflammation in accordance with their respective effect on MMP-9.